Constance Friess essay - Friess, Constance, 1908-
Essay concerning Friess's relations with Georgia O'Keeffe as her friend and physician. Also discusses O'Keeffe's relations with Doris Bry, Juan Hamilton, and O'Keeffe's husband, Alfred Stieglitz.
Physician of New York (N.Y.).
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Bry, Doris; Hamilton, Juan; O'Keeffe, Georgia, -- 1887-1986.; Stieglitz, Alfred, -- 1864-1946.; Artists; Medicine -- Practice -- New York (State) -- New York; Physicians